Chromosomal Instability at Fragile Sites in Blue Foxes, Silver Foxes, and Their Interspecific Hybrids - Kuchta-Gładysz, Marta (Animals (Basel), 2021)
SIMPLE SUMMARY: The paper describes the karyotypes of blue and silver foxes and their hybrids, in terms of the numbers of A and B chromosomes and the frequency of fragile sites on chromosomes. Genome stability in these species is affected by Robertson translocations in the karyotype of the blue fox and by B chromosomes in the silver fox. The fragile sites assay was used as a biomarker to assess genome stability in foxes. This test enables the identification of breaks, chromatid gaps, and deletions. In healthy individuals, the number of these instabilities remains low. The test can be used to select individuals with the most stable genome for breeding of blue and silver foxes. The fewer an individual’s susceptible sites, the more likely it is to have good reproductive performance. This factor is extremely important in the case of blue foxes, which are an endangered species. ABSTRACT: A cytogenetic assay based on fragile sites (FS) enables the identification of breaks, chromatid gaps, and deletions. In healthy individuals, the number of these instabilities remains low. Genome stability in these species is affected by Robertsonian translocations in the karyotype of the blue fox and by B chromosomes in the silver fox. The aims of the study were to characterise the karyotype of blue foxes, silver foxes, and their hybrids and to identify chromosomal fragile sites used to evaluate genome stability. The diploid number of A chromosomes in blue foxes ranged from 48 to 50, while the number of B chromosomes in silver foxes varied from one to four, with a constant number of A chromosomes (2n = 34). In interspecific hybrids, both types of karyotypic variation were identified, with the diploid number of A chromosomes ranging from 40 to 44 and the number of B chromosomes varying from 0 to 3. The mean frequency of FS in foxes was 4.06 ± 0.19: 4.61 ± 0.37 in blue foxes, 3.46 ± 0.28 in silver foxes, and 4.12 ± 0.22 in hybrids. A relationship was identified between an increased number of A chromosomes in the karyotype of the hybrids and the frequency of chromosomal breaks. The FS assay was used as a biomarker for the evaluation of genomic stability in the animals in the study.